Factors Influencing on Career Choices of Undergraduate Students - Madhusankha, Y. P.; Karunarathne, R. A. I. C. (Faculty of Commerce and Management Studies, University of Kelaniya Sri Lanka, 2022)
One of the most significant stages in life is choosing a career because it will decide the type of role that person will need to perform in society in the future. The purpose of this study is to investigate the factor influencing undergraduates' career decisions. To attain this objective, we collected data from 254 management undergraduates who are studying their final year of their degree programme, at the University of Kelaniya, Sri Lanka. Undergraduate students were chosen since they would be faced with the decision of what career to pursue as soon as they graduated. Data were analyzed using linear regression and the results showed that undergraduates career choice depends on self-efficacy, family, personal interests, and economic factors. Thus, the findings of this study are theoretically and practically significant. The main limitation of this study is that this study focused only on management undergraduates, however, the results might be varied with other disciplines. Therefore, we encourage future researchers to test our model across different samples.
Keywords: Undergraduate Students, Career Choices, University of Kelaniya, self-efficacy, Family influence, personal interest, economic consideration